Pembuatan Desain Smartship untuk Perjalanan dari Pantai Indramayu - Boedi Herijono; Sutrisno, Imam; Projek Priyonggo; Fahmi Umasangadji; Ardiansyah; Dedy Hidayat Kusuma (CV. Creative Tugu Pena, 2024)
This research aimed to design an efficient and environmentally friendly smartship to support maritime transportation activities in Pantai Indramayu. Research methods included literature review, 3D modeling, and numerical simulation. Results demonstrated that the proposed smartship design can reduce fuel consumption by up to 20% compared to conventional vessels of similar size. Additionally, the developed autonomous navigation system enables the ship to operate independently under various weather conditions. In conclusion, this smartship design holds significant potential to enhance operational efficiency and reduce environmental impact within Indonesia's maritime industry